A two-phase adaptive finite element method for solid–fluidcoupling in complex geometries - Garcia,X; Pavlidis,D; Gorman,GJ; Gomes,JLMA; Piggott,MD; Aristodemou,E; Mindel,J; Latham,JP; Pain,CC; ApSimon,H (International Journal for Numerical Methods in Fluids, 2010)
In this paper we present a method to solve the Navier–Stokes equations in complex geometries, suchas porous sands, using a finite-element solver but without the complexity of meshing the porous space.The method is based on treating the solid boundaries as a second fluid and solving a set of equationssimilar to those used for multi-fluid flow. When combined with anisotropic mesh adaptivity, it is possibleto resolve complex geometries starting with an arbitrary coarse mesh. The approach is validated bycomparing simulation results with available data in three test cases. In the first we simulate the flow pasta cylinder. The second test case compares the pressure drop in flow through random packs of sphereswith the Ergun equation. In the last case simulation results are compared with experimental data on theflow past a simplified vehicle model (Ahmed body) at high Reynolds number using large-eddy simulation(LES). Results are in good agreement with all three reference models.